(untitled) (Miscelânea: Journal of Literature and Social Life, 2024)
We had the privilege of engaging in dialogue with Dr. Chrysogonus Siddha Malilang, a senior lecturer at the Faculty of Education and Society at the University of Malmo, specializing in Literary Studies, Children’s Literature, and Creative Writing. With a diverse academic background, including a PhD in Literary Studies (English), Chrysogonus brings a wealth of knowledge and experience to our academic conversation. Dr. Malilang’s research spans a variety of intriguing topics, including Creative Writing Pedagogy, Play in Education, Critical Pedagogy, Community of Practice, and a/r/tography. Additionally, he investigates the confluence of Children’s Literature and New Media, exploring unconventional formats such as graphic novels and video games. As an experienced author, with creative works ranging from novels to poetry books, his literary contributions have resonated with audiences in Macau, Sweden, and Indonesia. Our dialogue will examine some of Dr. Malilang’s recent academic contributions, shedding light on articles addressing the re-appropriation and alteration of old children’s literature in ongoing teaching practices. Furthermore, we will delve into his active involvement in research initiatives, particularly in the implementation of Visual Thinking Strategies (VTS) in Swedish Early Childhood Education and the exploration of a/r/tography within the intersections of education and the arts.